2009
DOI: 10.1063/1.3271682
|View full text |Cite
|
Sign up to set email alerts
|

⟨ 001 ⟩ textured (K0.5Na0.5)(Nb0.97Sb0.03)O3 piezoelectric ceramics with high electromechanical coupling over a broad temperature range

Abstract: ⟨ 001 ⟩ -oriented (K0.5Na0.5)(Nb0.97Sb0.03)O3 (KNNS) ceramics with a narrow orientation distribution (full width at half maximum=7.0°) were produced by templated grain growth using NaNbO3 templates. Excellent electromechanical properties were obtained from −70 °C to the polymorphic phase transition (PPT) at 160 °C. Textured KNNS ceramics show very high electromechanical coupling factors kp=0.64 and k31=0.37, high piezoelectric constants d33=208–218 pC/N and d31=−82 pC/N, and modest strain hysteresis (6.3%) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
95
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 16 publications
5
95
2
Order By: Relevance
“…Special attention was given to the excellent temperature stability of electromechanical properties of the textured KNN-based ceramics. So far, a number of research works on the effect of grain texturing both for KNN-based [20][21][22] and BNT-based [23][24][25][26][27][28][29][30][31][32] systems have been reported, casting perspectives for potential use for high-valued applications. In the meantime, tuning the phase transition temperature from orthorhombic to tetragonal by chemical modification has revealed that even the properties of bulk KNN can be greatly enhanced, though KNN still suffers a significant temperature-dependent variation in functional properties [33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Special attention was given to the excellent temperature stability of electromechanical properties of the textured KNN-based ceramics. So far, a number of research works on the effect of grain texturing both for KNN-based [20][21][22] and BNT-based [23][24][25][26][27][28][29][30][31][32] systems have been reported, casting perspectives for potential use for high-valued applications. In the meantime, tuning the phase transition temperature from orthorhombic to tetragonal by chemical modification has revealed that even the properties of bulk KNN can be greatly enhanced, though KNN still suffers a significant temperature-dependent variation in functional properties [33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Texture control of polycrystals is an important approach to improve the piezoelectric properties of lead free materials without drastically changing the composition of the ceramics. There have been several grain orientation methods, such as oriented consolidation of anisometric particles [18], templated grain growth (TGG) [16], reactive templated grain growth (RTGG) [12], directional solidification technology [19] and multilayer grain growth technology [4] and so on. Among these methods, (R)TGG proves to be suitable for a material with cubic symmetry, particularly for perovskite structure materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to replace the Pb-contained piezoceramics, it has been thought that some techniques to enhance the piezoelectric performance must be needed. The electrical properties of KNN ceramics have been observably improved by composition designing [2][3][4][5][6], doping [7][8][9][10][11] or grain orientation methods [12][13][14][15][16][17]. Texture control of polycrystals is an important approach to improve the piezoelectric properties of lead free materials without drastically changing the composition of the ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…56 Although both the M A and M B phases belong to the Cm space group, the difference lies in the magnitudes of the components of the polarization corresponding to the pseudocubic cell: for the M A phase, Px ¼ Py < Pz, whereas for the M B phase, Px ¼ Py > Pz. 56 The excellent piezoelectric properties of h001i grainoriented KNN-based ceramics 1,5 for compositions close to the PPB may be the result of "domain-engineered" states, whose structural origins are as yet unidentified. In order to elucidate the mechanism for high piezo-responses in the KNN-based non-Pb systems, it is important to develop a structural understanding of induced phase transitions in the PPB region.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In particular, some (K,Na,Li)(Nb,-Ta,Sb)O 3 ceramics exhibit longitudinal piezoelectric coefficients of d 33 ! 400 pC=N, 1,13 which is nearly comparable with that of "soft" Pb(Zr,Ti)O 3 materials such as PZT-5A.…”
Section: Introductionmentioning
confidence: 99%